THE ROLE OF STATE IN FORMING THE SMALLAND LARGE-SIZE BUSINESS INTEGRATION IN INNOVATIVE SPHERE - S. G. Avdonina; S. I. Grudina; A. I. Podgornaya (Russian Journal of Economics and Law)
Objective: to analyze the influence of state on the small- and large-size business integration in the sphere of innovations. Methods: analysis and synthesis; statistical and abstract-logical. Results: direct and indirect methods of influence are revealed on the development of integration links of the small and large-size business in innovative sphere. Scientific novelty: the approach is suggested to classify the methods of influence on innovative processes activization, which, unlike the known approaches, views the state influence on the development of integration relations of the small- and large-size business in innovative sphere. Practical value: the suggested methods are aimed at improving the state innovative policy and transition towards economic development based on own innovations. It is stated that indirect mechanisms are more relevant in Russia.